A evolução da relação bilateral Brasil-Argentina na temática nuclear (2003-2018) - Pacheco, João Marcos Ferreira (2022)
The bilateral relation between Brazil and Argentina in the nuclear field has been the object of investigation of researchers and observers since the beginning of their respective nuclear programs. The two countries went through moments of competition and rivalry until the decade of 1980, when a movement of political rapprochement was mutually sought, which led to a process of integration and cooperation in the nuclear field. This process originated the Brazilian-Argentinian Agency for Account and Countability of nuclear materials (ABACC), which became a model of crossed inspections of nuclear facilities responsible for building trust between the two countries and before the international community. The specialized literature observes points of coincidence in terms of positionings before the Nuclear Nonproliferation Regime and of objectives related to nuclear development: both countries did not sign the Treaty on the Nonproliferation of Nuclear Weapons (NPT) and kept themselves at the margins of the Regime until the decade of 1990, coordinating policies to resist international pressures. In the 1990s, due to domestic and systemic conjectures, both countries signed the NPT and take part in the Nonproliferation Regime. This dissertation seeks to analyze the bilateral relation in the nuclear field from 2003 to 2018. We argue that this relation is best understood through an analysis of the antecedents of the Brazilian and Argentinian nuclear programs and an understanding of the foreign policies implemented by each country during such period, which respond to objectives and interests particular to each government. We conclude that the bilateral cooperation was kept stable in relation to the maintaining of ABACC and the commitments to mutual trust building; that there was a smaller degree of policy coordination when facing the international mechanisms, in relation to the period of 1960-1990, and that the bilateral cooperation found limits in relation to projects of joint technical and technological development, which would include the transfer of technology, due to particularities of each nuclear program in respect to their guidelines, objectives and actors